2006
DOI: 10.1007/s10461-005-9044-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexually Transmitted Infection Testing Among Sexually Active Homeless Youth

Abstract: We examined the association between sexual risk behaviors and sexually transmitted infection (STI) testing in a sample of homeless youth. Of 261 youth interviewed, 50% had been sexually active in the past 3 months. Gender variation in sexual behaviors and risk were found. Boys were more likely than girls to engage in anal sex (46% vs. 15%), to have 3 or more sexual partners (46% vs. 17%) and to engage in anonymous sex (38% vs. 21%). Girls were less likely to use condoms consistently and more likely to engage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
4
14
1
1
Order By: Relevance
“…Although our overall rate of LPI was within the range documented by other studies, 8,9,[20][21][22][23] LPI rates for males and for females with certain risky sexual behaviors were higher than those previously reported. For example, the rates of LPI among females with histories of sex exchange (76%) and STI (61%) observed in our assessment are higher than rates from previous reports (2-43% and 6-45%, respectively).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although our overall rate of LPI was within the range documented by other studies, 8,9,[20][21][22][23] LPI rates for males and for females with certain risky sexual behaviors were higher than those previously reported. For example, the rates of LPI among females with histories of sex exchange (76%) and STI (61%) observed in our assessment are higher than rates from previous reports (2-43% and 6-45%, respectively).…”
Section: Discussionsupporting
confidence: 65%
“…22,23 Furthermore, most of the earlier research exploring LPI among street and homeless youth has been conducted among females only. 18,20,22,23,28 Although three studies have included males, 8,9,21 the only one to report LPI separately by gender found 10% LPI in a small sample of 50 males. 9 We found a higher prevalence of LPI in our sample of 706 male street youth (24%), which is likely an underestimate given that male knowledge of partner pregnancy may be incomplete, especially in the setting of multiple partners.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers studying homeless youth have examined correlates of non-condom use 10 and HIV or STI testing, 14,17 and have focused on STI as one of many dependent variables associated with numerous outcomes such as sexual risk or depression. 9,18 Others have looked at the frequency of risky behaviors including STI but many of these studies are descriptive and have not gone beyond correlates and means tests; 12,13,19 therefore, very few studies have focused specifically on risk factors associated with contracting STI among homeless youth.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-five percent of women and 40% of men aged 25-44 reported ever having heterosexual anal sex (HAS) (Mosher, Chandra, Jones, & Division of Vital Statistics, 2002). Anal sex carries a greater risk for women than vaginal intercourse (Misegades et al 2001;Voeller, 1991) with respect to HIV transmission, yet research has found that women underestimate the risks of anal sex (Halperin, 1999), and are less likely to use condoms during anal intercourse than vaginal intercourse (Misegades & Page-Shafer, 2001;Solorio, Milburn, Rotheram-Borus, Higgins, & Gelberg, 2006). In fact, seven times more women than homosexual men engage in unprotected receptive anal sex (Halperin).…”
Section: Introductionmentioning
confidence: 99%